Evaluation of Cases Belonging to Youths Autopsied in Muğla - Balcı, Yasemin; Kadı, Gülsüm; Erbaş, Melike; Göçeoğlu, Ümit Ünüvar (The Bulletin of Legal Medicine, 2018)
Objective:The objective of this study was to evaluate the cases belonging to youths autopsied in Muğlaand to reveal regional profile of deaths in forensic cases to make suggestions by evaluating these cases. Materials and Method:We retrospectively evaluated the autopsy reports of 162 (%10,1) cases belonging to the age group of 15-24 years; out of 1603 autopsies that were done in Muğla Directorate of Forensic Medicine Institute between the years of 2013 and 2016 Findings:The frequency of this age group was higher in 2015 with 59 cases and in 2016 with 39 cases. The 82,7% of cases was men and 17,3% was women, there were 76 cases (46,9%) belonging to the age group of 15-19 years and 86 cases (53,1%) belonging to the age group of 20-24 years. The 75,3% of cases was having Turkish nationality and the rest were foreigners. The cases were mostly sent from Bodrum, Fethiye and Milas accordingly. The events were reported as sudden unexpected for 23 cases, emerged from water for 50 cases, firearm for 19 cases and various accidents for 45 cases. The causes of deaths were reported for 51 cases (31,5%) as drowning, for 10 cases (6,2%) as natural causes, for 90 cases (55,5%) as violent death and for 11 cases (6,8%) as unidentified causes. There were 12 (7,4%) decayed cases, 10 of these were emerged from water. In toxicological analysis alcohol was found in blood for 44 cases and for 15 of these alcohol was found also in vitreous fluid. Results and Conclusions